Health and Academic Achievement 2018
DOI: 10.5772/intechopen.73580
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resilience and Psychological Well-Being in School Engagement and Perceived Academic Performance: An Exploratory Model to Improve Academic Achievement

Abstract: The aim of the present study is to examine the relationship between resilience, subjective well-being and academic achievement (i.e., school engagement and perceived performance). To achieve this, a battery of instruments was applied to 945 Compulsory Secondary Education students from Basque Country (425 boys and 520 girls) of medium socio-cultural level and aged between 12 and 17 (M age = 14.50, SD = 1.82). The study tests a structural model for analyzing the effects of resilience and subjective well-being on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 62 publications
6
33
0
5
Order By: Relevance
“…Of the few studies which have explored this association, one conducted with a population of young immigrants found that those who believed they were doing well at school scored significantly higher for resilience [45], and another [46] found that resilience predicted perceived academic performance among university students, both directly and indirectly through coping. Similarly, Rodríguez-Fernández et al [47] found a relationship between resilience and perceived academic performance which was mediated by subjective wellbeing and school engagement.…”
Section: Resilience As a Mediator Variablementioning
confidence: 89%
“…Of the few studies which have explored this association, one conducted with a population of young immigrants found that those who believed they were doing well at school scored significantly higher for resilience [45], and another [46] found that resilience predicted perceived academic performance among university students, both directly and indirectly through coping. Similarly, Rodríguez-Fernández et al [47] found a relationship between resilience and perceived academic performance which was mediated by subjective wellbeing and school engagement.…”
Section: Resilience As a Mediator Variablementioning
confidence: 89%
“…This finding highlights the complex relationship between resilience and well-being. Several studies have shown that resilience is positively correlated with psychological well-being and vice versa, however, the directional causality of resilience and well-being has not been clearly explored ( Fredrickson and Joiner, 2002 ; Mak et al, 2011 ; Souri and Hasanirad, 2011 ; Rodriguez-Fernandez et al, 2018 ; Liu et al, 2020 ; Wu et al, 2020 ). A study conducted with Chinese college students found further support for the reciprocal relationship between resilience and mental health status, indicating that resilience predicted the level of mental health and vice versa within 1 year from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez et al (2018) in their study conducted showed that there are several variables that need to be consider in understanding resilience and academic performance. Fernandez et al (2018) presented that subjective well-being and school engagement act simultaneously as mediator variables between perceived academic performance and 478 resilience. This suggests that perceiving oneself as being able to cope successfully with adverse situation has a significant impact on the young personal and school related adaptation.…”
Section: Mediators Between Resilience and Academic Performancementioning
confidence: 99%